Miniinvasive Techniques in Rhinoplasty - Serdev, Nikolay (IntechOpen, 2016)
This book is divided into two parts. The first part describes mini-invasive surgical techniques, sufficient to perform the most important tasks in rhinoplasty, such as: tip rotation and projection; closure of the open roof after humpectomy; alignment and stabilization of the columella; refinement of the nasal tip, lower third and medial third; narrowing of the alar base. The second part concerns medical rhinoplasty techniques using nerve blocks, injectable fillers etc., which aim is to achieve similar results, despite their temporary effect. Currently, the request for such procedures and their number exceeds this of surgical operations and demonstrates their importance. Although minimally invasive techniques will not totally replace surgical rhinoplasty, this book will serve as a tool to enhance refinement of rhinoplasty and clinical aesthetics.This first textbook in minimally invasive rhinoplasty techniques will be of great help to many doctors and will provoke further development of time-saving, atraumatic and mini-invasive techniques with preservative attitude toward nasal tissues in the modern art of nasal and face beautification.